Accelerated Decline in Javelin Throwing Performance in Master Athletes 70 Years and Older – Do Changes in Technique Play a Role? - Ganse, Bergita; Degens, Hans (Sports Medicine International Open, 2018)
While many older adults are immobile and frail, others still participate in competitive sports. World records of javelin throw decrease with increasing age. It is, however, unknown 1) whether the decline is linear or, as in sprint performance, accelerates beyond the age of 69; and 2) to what extent frailty-related changes in throwing technique contribute to decreasing performance. We plotted current world records against age and assessed the performance of 27 male javelin throwers 69 years and older during three master athletics championships. Three to six throws were filmed, and the best throw of each athlete selected. A step-wise linear regression was applied to assess contributions of age, angle of release, angle of attitude, angle of attack and elbow angle just before the pull to performance. The ageing-related decline in javelin-throw performance accelerated after age 69. Age was the main predictor of performance (adjusted R2=0.68), with a small contribution of elbow angle (adjusted R2 increased to 0.76) and angle of attack (R2=0.82; all P<0.001) in the older athletes. None of the technique-related parameters correlated with age. Although the technique had some influence on javelin-throwing performance, the accelerated decline was not associated with a characteristic ageing-related change in technique.
Keywords: age; athletics; video; biomechanics; ageing; javelin; throwing